PENGARUH MODEL PEMBELAJARAN SNOWBALL THROWING BERBANTUAN MEDIA KOTAK BELAJAR AJAIB PERKALIAN (KOBELA) TERHADAP HASIL BELAJAR SISWA PADA MATERI PERKALIAN KELAS II SD NEGERI GAROT ACEH BESAR - Mega novia; Tursinawati; Linda Vitoria (STKIP Subang, 2026)
The mathematics learning process for multiplication in second grade at Garot State Elementary School in Aceh Besar still faces various challenges, such as teachercentered instruction without the use of concrete learning materials. Students struggle to understand the concept of multiplication due to rote memorization methods, a lack of variety in learning strategies, and limited access to supportive learning materials. This study aims to determine the effect of the Snowball Throwing learning model assisted by the Magic Multiplication Learning Box (KOBELA) on the learning outcomes of second-grade students at Garot State Elementary School in Aceh Besar. This study uses a quantitative approach with aquasi-experimental design employing a non-equivalent control group design. The population in this study consists of all second-grade students at Garot State Elementary School in Aceh Besar, with Class 2A serving as the experimental class and Class 2B as the control class. The results indicate that the average post-test scores of students in the experimental class, which implemented the Snowball Throwing learning model assisted by the KOBELA media, were higher than those in the control class, which used conventional instruction. The results of the independent sample t-test showed a significance value (2-tailed) of 0.000 < 0.005, so it can be concluded that there is an effect on mathematics learning outcomesin the class that implemented the snowball throwing model assisted by Kobela media at Garot State Elementary School in Aceh Besar.